CD8+ T-Cell Exhaustion Phenotype in Chronic Hepatitis C Virus Infection Is Associated With Epitope Sequence Variation - Osuch, Sylwia; Laskus, Tomasz; Perlejewski, Karol; Berak, Hanna; Bukowska-Ośko, Iwona; Pollak, Agnieszka; Zielenkiewicz, Magdalena; Radkowski, Marek; Caraballo Cortés, Kamila (Frontiers in Immunology, 2022)
Background&Aims During chronic hepatitis C virus (HCV) infection, CD8+ T-cells become functionally exhausted, undergoing progressive phenotypic changes, i.e., overexpression of “inhibitory” molecules such as PD-1 (programmed cell death protein 1) and/or Tim-3 (T-cell immunoglobulin and mucin domain-containing molecule-3). The extreme intrahost genetic diversity of HCV is a major mechanism of immune system evasion, facilitating epitope escape. The aim of the present study was to determine whether T-cell exhaustion phenotype in chronic HCV infection is related to the sequence repertoire of NS3 viral immunodominant epitopes. Methods The study population was ninety prospective patients with chronic HCV genotype 1b infection. Populations of peripheral blood CD8+ T-cells expressing PD-1/Tim-3 were assessed by multiparametric flow cytometry, including HCV-specific T-cells after magnetic-based enrichment using MHC-pentamer. Autologous epitope sequences were inferred from next-generation sequencing. The correction of sequencing errors and genetic variants reconstruction was performed using Quasirecomb. Results There was an interplay between the analyzed epitopes sequences and exhaustion phenotype of CD8+ T-cells. A predominance of NS31406 epitope sequence, representing neither prototype KLSGLGLNAV nor cross-reactive variants (KLSSLGLNAV, KLSGLGINAV or KLSALGLNAV), was associated with higher percentage of HCV-specific CD8+PD-1+Tim-3+ T-cells, P=0.0102. Variability (at least two variants) of NS31406 epitope sequence was associated with increased frequencies of global CD8+PD-1+Tim-3+ T-cells (P=0.0197) and lower frequencies of CD8+PD-1-Tim-3- T-cells (P=0.0079). In contrast, infection with NS31073 dominant variant epitope (other than prototype CVNGVCWTV) was associated with lower frequency of global CD8+PD-1+Tim-3+ T-cells (P=0.0054). Conclusions Our results indicate that PD-1/Tim-3 receptor expression is largely determined by viral epitope sequence and is evident for both HCV-specific and global CD8+ T-cells, pointing to the importance of evaluating autologous viral epitope sequences in the investigation of CD8+ T-cell exhaustion in HCV infection.